Serratia osteomyelitis and chronic granulomatous disease. - Campos, Manuela (2011)
Chronic Granulomatous Disease (CGD) is a primary immunodeficiency disorder characterized by recurrent purulent infections of the skin, lungs, and reticuloendothelial organs, primarily due to staphylococci, enteric bacteria, fungi, and occasionally mycobacteria. More than two thirds of all cases are X-linked and result from defects in the CYBB gene that encodes the gp91-phox subunit of NADPH oxidase. The authors present a case of a three month old child admitted with a metacarpic steomyelitis by Serratia marcescens. Studies confirmed an abnormal respiratory burst in activated neutrophils and absence of gp91-phox expression on patient and a brother (with previous Nocardia infection). Both hemizygous for a pathogenic mutation detected in exon 3 of CYBB gene (c.252 G>A, p.Ala84Ala), a variant that affects the splicing. At two years of age he is still on prophylaxis with cotrimoxazol and itraconazol, without relevant complications. CGD is rare but must be evocated in cases of uncommon or atypical infections.